Eksistensi Surat Penawaran Putusan Kredit (SPPK) dalam Perjanjian Kredit yang Memuat Klasula Baku Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Kantor Cabang Bintaro - Yenedy, Ringgo; Azheri, Busyra; Mannas, Yussy A. (Universitas Ekasakti, 2025)
In common banking practice in Indonesia, the bank credit agreement used is a standard agreement or standard agreement, the clauses of which have been previously prepared by the bank, so that the customer as a prospective debtor only has the choice between accepting the entire contents of the clauses, either in part or completely or refuse, which will result in the customer not receiving the credit. As risk mitigation in implementing standard agreements, debtors are given a credit decision offer letter more commonly called an offering letter. An credit decision offering letter is a bank offer letter for credit approval addressed to the debtor. If the debtor agrees, then the offering letter is used as the basis for making a credit deed.